Vascular flora and social interest urbanization in Villavicencio: conflicts with the biodiversity conservation (2019)
Colombia presents around 24,530 species of vascular plants. However, this floristic richness is declining or showing some degree of threat, because their habitat has been reduced by the development of anthropic activities as urbanization, mining, agrarian and other. This same trend is observed in Villavicencio. For this reason, the present research has as objective to describe the floristic diversity remaining in the water rounds of Caño Zuria and La Madrid wetland located in the neighborhood of the same name. To carry out the research, opportunistic samplings were made where plant material in reproductive state was collected and species were identified. As results, it was found that the flora associated with the La Madrid wetland has 19 species of vascular plants grouped into 13 families, with Poaceae being the best represented. Of the registered species there are two that are in the category of least concern concern (LC), which are Andropogon bicornis and Jamaican Solanum. In the flora associated with the water round of the Zuria canal, 21 vascular plant species were found grouped into 11 families, of which the dominant one was Melastomaceae with six species, followed by Araceae with three species. Of the registered species, Psychotria poeppigiana is in the category of minor concern threat (LC). The analyzes carried out show that unsustainable urban development threatens the biodiversity of the flora and the supply of ecosystem services associated with the water rounds of the Zuria canal and La Madrid wetland in the municipality of Villavicencio.